Application of machine learning to predict the properties of Bi2Te3 -based thermoelectric materials - Anatychuk, L.I.; Korop, M.M. (Journal of Thermoelectricity, 2023)
The paper provides examples of assessing the effectiveness of machine learning for predicting the properties of Bi2Te3-based thermoelectric materials. The results of their application and methods for selecting optimal input data parameters are considered, the differences and features of choosing algorithms, the stages of work and training machine models, as well as the criteria for assessing the effectiveness and validation of the obtained forecasts are described.